Energy-dense, low-fiber, high-fat dietary pattern is associated with increased fatness in childhood. - Johnson, L; Mander, A; Jones, L; Emmett, P; Jebb, SA (2008)
BACKGROUND: Evidence for the dietary determinants of obesity in children is limited. OBJECTIVE: The objective was to identify a dietary pattern that explained dietary energy density (DED), fiber density (FD), and percentage of energy intake from fat and analyze its relation to fatness in children. DESIGN: The subjects were 521 (at ages 5 and 9 y) and 682 (at ages 7 and 9 y) children participating in the Avon Longitudinal Study of Parents and Children. Diet was assessed with the use of 3-d diet diaries at ages 5 and 7 y. Reduced rank regression derived a dietary pattern with the use of DED, fiber, and fat intake as intermediate variables. Fat mass was measured at age 9 y with the use of dual-energy X-ray absorptiometry. Fat mass index (FMI) was calculated, and excess adiposity was defined (as the top quintile of logFMI). RESULTS: Pattern score at ages 5 and 7 y was correlated with DED (r = 0.8), FD (r = -0.7), and percentage of energy intake from fat (r = 0.5). An increase of 1 SD of pattern score at ages 5 and 7 y, respectively, was associated with a 0.15-kg (95% CI: -0.1, 0.45 kg) and a 0.28-kg (95% CI: 0.05, 0.53 kg) higher fat mass at age 9 y, after controlling for confounders. The adjusted odds of excess adiposity at age 9 y for children in quintile 5 compared with quintile 1 of dietary pattern score at ages 5 and 7 y, respectively, were 2.52 (95% CI: 1.13, 6.08) and 4.18 (95% CI: 2.07, 9.38). CONCLUSION: An energy-dense, low-fiber, high-fat diet is associated with higher fat mass and greater odds of excess adiposity in childhood.